Strategi Penanganan Konflik pada Proses Penggabungan Perguruan Tinggi Swasta - Nidya Dudija (Psikohumaniora: Jurnal Penelitian Psikologi, 2018)
Abstract: Merger of academies to be one university is a way to perform effectivity and efficiency of the foundation as the organizer of education. The process of conveying the idea will face challenges and conflicts such as opposition to the idea of merging universities. Conflict can be a functional and dysfunctional role in the organization, depending on how the organization is able to manage the conflict and use appropriate conflict management strategies. The research was conducted at one of the private universities in Bandung that has combined four academies to form the University. This research uses a qualitative approach case study. The results of this study indicate that the foundation has an important role during the merging process, the foundation selects direct leaders (Rector of the University) from external parties to facilitate the process of forming a new culture, then the Foundation manages the conflict using a compromise strategy and collaboration to all academic communities so that conflicts arise functional role and improve post-merge University performance.Abstrak: Penggabungan sekolah tinggi menjadi universitas adalah salah satu cara untuk melakukan efektifitas dan efisiensi yayasan sebagai penyelenggara pendidikan. Proses menyampaikan ide akan menghadapi tantangan dan konflik seperti oposisi terhadap gagasan menggabungkan universitas. Konflik dapat berperan fungsional dan disfungsional dalam organisasi, tergantung pada bagaimana organisasi mampu mengelola konflik dan menggunakan strategi manajemen konflik yang tepat. Penelitian ini dilakukan di salah satu universitas swasta di Bandung yang telah menggabungkan empat sekolah tinggi untuk membentuk universitas. Penelitian ini menggunakan pendekatan kualitatif case study. Hasil penelitian ini menunjukkan bahwa yayasan memiliki peran penting selama proses penggabungan, yayasan memilih langsung pemimpin (Rektor Universitas) dari pihak eksternal untuk memfasilitasi proses pembentukan budaya baru, kemudian Yayasan mengelola konflik menggunakan strategi kompromi dan kolaborasi untuk semua komunitas akademis sehingga konflik muncul peran fungsional dan meningkatkan kinerja universitas pasca-penggabungan.